Advance of Mesenchymal Stem Cells in Chronic End-Stage Liver Disease Control - Yun Gao; Xiushan Yin; Xiaomeng Ren (Stem Cells International)
The chronic liver diseases will slowly develop into liver fibrosis, cirrhosis, and even liver cancer if no proper control is performed with high efficiency. Up to now, the most effective treatment for end-stage liver diseases is liver transplantation. However, liver transplantation has the problems of donor deficiency, low matching rate, surgical complications, high cost, and immune rejection. These problems indicate that novel therapeutic strategies are urgently required. Mesenchymal stem cells (MSCs) are somatic stem cells with multidirectional differentiation potential and self-renewal ability. MSCs can secrete a large number of cytokines, chemokines, immunomodulatory molecules, and hepatotrophic factors, as well as produce extracellular vesicles. They alleviate liver diseases by differentiating to hepatocyte-like cells, immunomodulation, homing to the injured site, regulating cell ferroptosis, regulating cell autophagy, paracrine effects, and MSC-mitochondrial transfer. In this review, we focus on the main resources of MSCs, underlying therapeutic mechanisms, clinical applications, and efforts made to improve MSC-based cell therapy efficiency.